Developing Healthy Thinking in Students as a Pedagogical Problem - Saydulloyevich, Ochilov Yakub; Shavkatovna, Kholova Mohigul (European Journal of Life Safety and Stability (2660-9630), 2021)
This article provides information on important aspects of developing healthy thinking in students through the pedagogical views of Eastern scholars.